THE RELATIONSHIPS BETWEEN MOTHER AGES, AGE OF PREGNANCY AND GRAVIDA THROUGH THE INCIDENT OF PREEKLAMPSIA IN RSUD HOSPITAL: HUBUNGAN USIA IBU, USIA KEHAMILAN DAN GRAVIDA DENGAN KEJADIAN PREEKLAMPSIA DI RSUD KOTA BOGOR - Desi Desi Nurseha Meirita (Jurnal Ilmiah Wijaya, 2018)
Based on the 2016 National Health Indicator Survey the maternal mortality rate in Indonesia is still high at 305 dead mothers per 100,000 people. The high maternal mortality rate was influenced by 28.8% due to preeclampsia. With the SDGs planned, 13 targets in point number three, one of which mentions by 2030, reduce maternal mortality to below 70 per 100,000 live births. Find out the correlation of maternal age, gestational age and gravides with the incidence of preeclampsia in RSUD Hospital Bogor in 2018. This type of research is analytical with retrospective research design. The researcher use 89 respondents to conudct this research. The Date collection is obtained by secondary methods, namely data taken from medical records. The analysis used is univariate, bivariate and multivariate analysis. Based on the results of the study found maternal age as many as 56 (62.9%) respondents, gestational age in the third trimester 70 (78.7%) respondents, multigravida as many as 59 (66.3%). Bivariate variables were found to correlate maternal age with the incidence of preeclampsia with p value of 0,004, The correlation of gestational age and the incidence of preeclampsia with p value of 0,069, The correlation of gravida with the incidence of preeclampsia with p value of 0,013. The results of multivariate analysis showed that the maternal age gravida variable had an opportunity of 0,013times greater than the gravida who experienced the incidence of preeclampsia. Maternal age variables have a greater chance of 3,006 times compared to the gravidaand gestational age that experienced the incidence of preeclampsia.